Intratendinous ganglion cyst of peroneus brevis tendon and its reconstruction with semitendinosus graft - Frangež, Igor; Nizič-Kos, Tea; Cimerman, Matej (Vojnosanitetski pregled, 2017)
Introduction. A ganglion cyst is a common benign tumor, mainly found in the wrist and ankle. The ones originating from a tendon, such as in our case, are the most rare. The ganglion cyst presents with a variety of symptoms, offering a wide range of possible differential diagnoses. Physical examination is crucial to make an accurate diagnosis, but magnetic resonance imaging (MRI) can help in identifying the ganglion cyst. The treatment is mostly conservative, but in cases when the ganglion cyst disables the patient’s ability for normal life functioning, due to pain and decreased mobility, surgery is necessary. Case report. A 38-year-old female with persistent ankle pain and edema was clinically diagnosed with luxation of peroneal tendons. Further investigation with MRI showed tenosynovitis of peroneal tendons and rupture of the superior peroneal retinaculum with an intratendinous ganglion cyst of peroneus brevis tendon. Surgical treatment with the reconstruction of peroneus brevis and peroneal retinaculum was performed with semitendinosus graft and anchor sutures. Histology confirmed the diagnosis of the intratendinous ganglion. After four months of rehabilitation, the patient returned to normal daily and sports activities and was pain-free on the follow-up. No recurrence of the ganglion cyst was acknowledged. Conclusion. Surgery is crucial for patients with intratendinous ganglion cyst and symptomatic instability of the peroneal tendons with chronic subluxation.